Dichotomous sperm in Lepidopteran insects: a biorational target for pest management - Seth, Rakesh K.; Yadav, Priya; Reynolds, Stuart E. (Frontiers in Insect Science, 2023)
Lepidoptera are unusual in possessing two distinct kinds of sperm, regular nucleated (eupyrene) sperm and anucleate (apyrene) sperm ('parasperm'). Sperm of both types are transferred to the female and are required for male fertility. Apyrene sperm play 'helper' roles, assisting eupyrene sperm to gain access to unfertilized eggs and influencing the reproductive behavior of mated female moths. Sperm development and behavior are promising targets for environmentally safer, target-specific biorational control strategies in lepidopteran pest insects. Sperm dimorphism provides a wide window in which to manipulate sperm functionality and dynamics, thereby impairing the reproductive fitness of pest species. Opportunities to interfere with spermatozoa are available not only while sperm are still in the male (before copulation), but also in the female (after copulation, when sperm are still in the male-provided spermatophore, or during storage in the female's spermatheca). Biomolecular technologies like RNAi, miRNAs and CRISPR-Cas9 are promising strategies to achieve lepidopteran pest control by targeting genes directly or indirectly involved in dichotomous sperm production, function, or persistence.